Glass-ionomer open exposure (GOPEX) versus closed exposure of palatally impacted canines: a retrospective study of treatment outcome and orthodontists' preferences. (1st June 2018) - Naoumova, Julia; Rahbar, Elmira; Hansen, Ken
Summary: Objectives: To investigate which surgical technique orthodontists prefer for exposing palatally impacted canines (PICs), and to compare closed exposure and glass-ionomer open exposure (GOPEX) with regard to pre- and post-surgical orthodontic variables. Materials and methods: A questionnaire with 19 questions and three cases visualising superficial, deep, or medial PICs was sent to 48 orthodontists working in a Swedish county. Sixty case records for patients with unilateral PICs from two centres were analysed; 30 patients having GOPEX (Centre A), and 30 undergoing closed exposure (Centre B). Pre- and post-surgical orthodontic variables were collected from the dental records. Results: The response rate was 81 per cent. There was an equal distribution of preference between open and closed exposure. Glass-ionomer cement (GIC) was predominately used as surgical packing in open exposure. No active traction was initiated until the canine erupted spontaneously. In the closed exposure cases, traction started shortly after exposure. The clinicians mentioned similar advantages of choosing one technique over the other and the main basis for the decision was the clinician's preference and not the location of the canine. There were no differences regarding post-exposure complications between the techniques. The overall treatment time was the same but there were fewer appointments and significantly shorter active treatment time with traction of the PIC in the GOPEX group. Limitations: Despite the homogeneity of the baseline patient characteristics, pre- and post-surgical orthodontic variables were analysed retrospectively, therefore, it is difficult to assess what impact these confounding factors may have had on the treatment time. Conclusions: The choice of exposure technique depends on the clinician's preferences. The active treatment time is shorter and the number of appointments fewer with open exposure when GIC is used as surgical packing.